2021
DOI: 10.1155/2021/6688549
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Influencing the Allocation of Regional Sci-Tech Financial Resources Based on the Multiple Regression Model

Abstract: This article uses a multiple regression model to evaluate the extent to which financial resources in various regions can be put into the most appropriate direction through the financial system or financial market. This paper uses the Tobit model to conduct empirical analysis on the input and output data of technology finance in multiple provinces and cities and explores the impact of various factors on technology finance efficiency from the perspective of three technology finance entities: high-tech enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…However, there was market failure in the R&D activities led by enterprises, and the national economic development needs to be guided by government policies. Under such backgrounds, on the basis of inheriting innovation theory, National System of Innovation, represented by Christopher Freeman and Richard R. Nelson, proposed that technological innovation was not only enterprises activities but also be driven by the national innovation system, which afected the allocation and efciency of innovation resources [8,9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there was market failure in the R&D activities led by enterprises, and the national economic development needs to be guided by government policies. Under such backgrounds, on the basis of inheriting innovation theory, National System of Innovation, represented by Christopher Freeman and Richard R. Nelson, proposed that technological innovation was not only enterprises activities but also be driven by the national innovation system, which afected the allocation and efciency of innovation resources [8,9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the primary productive forces, science and technology not only need financial industry support 19 but can also react to industry developments. 23 The deepening of technology market development means that technological transformation is accelerated. As the results of technological innovation are mostly invested in meeting practical needs, financial demands become diversified, 66 which expands the financial industry development scale 67 and guides financial industry funds to carbon emission reduction.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…22 Technology can also react to the financial industry's development. 23 Scientific and technological achievements can guide the rational allocation of funds, 24 control risks, 11 and steer the financial industry's development toward carbon emission reduction. To achieve the goal of “carbon peaking” and “carbon neutral”, the financial industry has been helping to reduce carbon emissions through various means.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al measured the allocation efficiency of scientific and technological financial resources in Hubei Province and found that the problem of low allocation efficiency of scientific and technological financial resources in Hubei Province is the low value of pure technical efficiency and small effect on scale efficiency [34]. Empirical research shows that the efficiency level of sci-tech finance is affected by the government and its policies, venture capital companies [35], human capital [36], infrastructure environment, education funds [37], the proportion of direct financing, and the incubation capacity of science and technology business incubators [38]. Da Fonseca, RS pointed out that the governments continue to play a critical and determining role in science, technology, and innovation financing whether through financial incentives, fiscal incentives, or a mix of both.…”
Section: Introductionmentioning
confidence: 99%